Effect of molecular orientation on biodegradability of poly(glycolide-co-epsilon-caprolactone) - Cho, DK; Park, JW; Kim, SH; Kim, YH; Im, SS (ELSEVIER SCI LTD, 2003)
The effect of orientation in the amorphous and crystalline region on the biodegradability of linear and star-shaped Poly(glycolide-co-epsilon-caprolactone)(PGCL) was studied in terms of the crystalline orientation, the crystallinity and thermal properties. Microstructual changes during hydrolysis of the drawn linear and star-shaped PGCL films were investigated using the conventional wide-angle X-ray diffraction equipped a fiber specimen attachment. The drawn star-shaped PGCL showed higher degradation rate than the drawn linear shaped and the degradation decreased with increasing draw ratio. During hydrolysis, the crystallinity for all the samples increased but the crystalline orientation decreased. In particular, the decrement of the crystalline orientation for star-shaped PGCL was higher than that of linear PGCL. (C) 2003 Elsevier Science Ltd. All rights reserved.
Keywords: CRYSTALLINE; DEGRADATION; POLYLACTIDE; GLYCOLIDE